2009
DOI: 10.3109/10641960903407025
|View full text |Cite
|
Sign up to set email alerts
|

Zigzagged Augmentation Index in Diabetes

Abstract: Although the patients with diabetic nephropathy suffered high cardiovascular risk, augmentation index (AI) in diabetic nephropathy has been poorly characterized. Cross-sectional studies were performed on 26 diabetic and 27 nondiabetic nephropathic patients. Home blood pressure was examined. In addition, blood pressure, pulse rate, and AI were measured in both supine and sitting positions. Patient backgrounds such as age, sex, sitting blood pressure, and pulse rate were similar between two groups. Circadian var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…ASCOT-CAFÉ study demonstrated the advantage of lower AI for better cardiovascular outcomes in hypertensive patients [9]. As discussed (bide infra), AI measured in the sitting position, however, may be inappropriately low in diabetic group possibly due to the presence of neuropathy [14]. Taken together, these observations could account for that the shortness of height, an important determinant of AI, but not AI itself, was picked up as a risk factor of mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ASCOT-CAFÉ study demonstrated the advantage of lower AI for better cardiovascular outcomes in hypertensive patients [9]. As discussed (bide infra), AI measured in the sitting position, however, may be inappropriately low in diabetic group possibly due to the presence of neuropathy [14]. Taken together, these observations could account for that the shortness of height, an important determinant of AI, but not AI itself, was picked up as a risk factor of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous data demonstrated that AI positively correlated to left ventricular mass Index in patients with nondiabetic CKD [27]. Our recent data demonstrated that patients with diabetic nephropathy manifested greater decreases in AI, brachial and central blood pressures when their postures alter from supine to sitting position than those with nondiabetic CKD [14]. The patient with diabetic nephropathy commonly suffers neuropathy as well [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical parameters including estimated glomerular filtration rate (eGFR), albuminuria, and home blood pressure were analysed over 6 months. 2 We welcome the patients to take breakfast on visiting day. The study was approved by the ethical committees of International University of Health and Welfare (No.…”
Section: Methodsmentioning
confidence: 99%
“…3 Our recent data also showed that drops in radial AI are greater in patients with diabetic nephropathy when posture was changed from a supine to a sitting position than those for non-diabetics. 4 We have previously demonstrated that PWV correlated to AI in stage 1-3 non-diabetic chronic kidney disease (CKD) patients. 5 PWV is known to rise as the stage of CKD advances.…”
Section: Introductionmentioning
confidence: 99%